Reflection on Student Collaboration Skills Assessment by Biology Teachers - Bowo Sugiharto; Nurul Hidayati (Postgraduate, University of Mataram, 2022)
Collaboration skill is a skill possessed by a person to work effectively in a team to achieve specific goals. Collaboration skills become essential for students to master because these skills become provisions for students to face global competition and improve social aspects. This study aims to identify how teachers measure student collaboration skills in biology at high schools in the Surakarta region. The research conducted was survey research with 76 Biology teachers in Soloraya consisting of 23 private school teachers and 53 public school teachers. The instrument used was a questionnaire in the form of a data collection form developed from collaboration skills based on NEA and P21. Analysis of questionnaire data using Rasch modeling. The analysis result shows that the item has a good reliability with a KR-20 value of 0.9. Based on the results of data analysis, biology teachers at public schools took more collaborative skill measurements of students than in private schools, especially in the aspects of responsibility and other respects